2020
DOI: 10.1525/collabra.347
|View full text |Cite
|
Sign up to set email alerts
|

Repetition Increases Perceived Truth Even for Known Falsehoods

Abstract: Repetition increases belief in false statements. This illusory truth effect occurs with many different types of statements (e.g., trivia facts, news headlines, advertisements), and even occurs when the false statement contradicts participants' prior knowledge. However, existing studies of the effect of prior knowledge on the illusory truth effect share a common flaw; they measure participants' knowledge after the experimental manipulation and thus conditionalize responses on posttreatment variables. In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 18 publications
(31 reference statements)
3
48
0
1
Order By: Relevance
“…Most importantly, repetition did not interact with knowledge level, either on its own, F (2, 154) = 0.20, p = .818, η p 2 = .00, or in conjunction with age, F (4, 154) = 0.27, p = .894, η p 2 = .01. As in prior research (Fazio, 2020; Fazio et al, 2015), prior knowledge did not protect against the illusory-truth effect. Repetition affected all statements equally.…”
Section: Resultsmentioning
confidence: 41%
See 2 more Smart Citations
“…Most importantly, repetition did not interact with knowledge level, either on its own, F (2, 154) = 0.20, p = .818, η p 2 = .00, or in conjunction with age, F (4, 154) = 0.27, p = .894, η p 2 = .01. As in prior research (Fazio, 2020; Fazio et al, 2015), prior knowledge did not protect against the illusory-truth effect. Repetition affected all statements equally.…”
Section: Resultsmentioning
confidence: 41%
“…A secondary goal of this research was to replicate previous research on the effects of prior knowledge on the illusory-truth effect. Studies have shown that repetition increases perceived truth, even when people have prior knowledge that contradicts the repeated falsehood (Fazio, 2020; Fazio et al, 2015), and that repetition affects belief similarly for both plausible and implausible statements (Fazio, Rand, & Pennycook, 2019). To confirm and extend these findings, we designed our stimuli so that each age group would have relevant prior knowledge for some statements and limited knowledge about others.…”
Section: Effects Of Prior Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Repeated false statements are given higher truth ratings even when they contradict participants' existing knowledge (Brashier et al, 2017;Fazio, 2020b;Fazio et al, 2015). In these studies, participants' existing knowledge is measured either before (Fazio, 2020b) or after (Fazio et al, 2015) they participate in a typical illusory truth experiment (e.g., "What is the name for a cyclone that occurs over land? Hurricane, Tornado, or I Don't Know").…”
Section: Prior Knowledgementioning
confidence: 99%
“…Second, delegitimization is practiced with the focus of negative elements of a discourse, the suppression of violations of common values, or negative descriptions of certain parties. Third, delegitimization can be placed on the issue of possible effects of discourse (Fazio, 2020)…”
Section: The Concept Of Firehose Of Falsehoodmentioning
confidence: 99%